Application of Thiol-Modified Silica Hybrid Monoliths for Hydrophilic Interaction Capillary Liquid Chromatography - Furqani, Dr. Firda; Ilona Bella; Prima Fitria Hillman; Lee Wah Lim (Sains Natural: Journal of Biology and Chemistry, 2026)
A silica hybrid monolithic column modified with Thiol-group were successfully prepared via “one-pot” approach; tetramethoxysilane and 3-mercaptopropyltrimethoxysilane were mixed together with the porogens in ice bath before being injected into the fused capillaries (0.032 mm I.D.). The composition of the porogens as well as the reaction time and temperature were optimized. The efficiency of the columns was evaluated by separating some polar biological compounds (i.e. thymine, uracil, adenine, adenosine, and cytidine) under hydrophilic interaction chromatography (HILIC) mode. Uracil, adenosine and cytidine were baseline-separated when the concentration of acetonitrile, which was used as the eluent, was more than 90%. It is also found that by increasing the acetonitrile concentration, the retention time of all analytes was increased, proving that typical HILIC separation mechanism was involved.